JUSTIFICATION OF THE PROBABILITY OF DETERMINING THE PRESENCE OF SIGNALS IN THE ENVIRONMENT OF THEIR PROPAGATION - Ivanchenko, Serhiy; Nekoz, Vasyl (Ukrainian Information Security Research Journal, 2024)
The substantiation of the impossibility of determining the presence of signals in the media of their distribution was carried out. A discrete-continuous channel was used as a model of the information distribution channel. Information was produced from a discrete source, where each of the information symbols was matched by discontinuous implementations that propagated through a continuous medium with interference. Reception of signals is carried out by means that can be effective. From the point of view of securing information from uncontrolled dissemination and ensuring its security in the distribution environment, as a rule, two factors are used: attenuation of the wave (signal) amplitude during its propagation in the physical environment; the distorting effect of interference that takes place in the medium of signal propagation and destroys its shape. However, the use of these factors, which could ensure complete, almost absolute security of information, is a difficult issue, if not impossible. After all, signals propagating in space, in accordance with the laws of physics, do so in the form of electromagnetic or other waves, or streams of elementary (charged) particles. They can spread over fairly long distances, and theoretically almost to infinity, the effectiveness of their interception is completely determined by the effectiveness of the means of reception. To solve this issue, which is widely used in information security management, there is a risk-oriented approach that does not require absolute security, but allows the possibility of not fulfilling the security requirement with a certain acceptable risk [2]. This risk, as a rule, is determined by the permissible losses that the owner of the assets can incur, and at the same time the effectiveness of production processes will not be disturbed.